On the Solutions of a System of Third-Order Rational Difference Equations - A. M. Alotaibi; M. S. M. Noorani; M. A. El-Moneam (Discrete Dynamics in Nature and Society)
The structure of the solutions for the system nonlinear difference equations xn+1=ynyn-2/(xn-1+yn-2), yn+1=xnxn-2/(±yn-1±xn-2), n=0,1,…, is clarified in which the initial conditions x-2, x-1, x0, y-2, y-1, y0 are considered as arbitrary positive real numbers. To exemplify the theoretical discussion, some numerical examples are presented.